Cross-temperature liquid hydrogen fuel cell power system
The cross-temperature range liquid hydrogen fuel cell power system addresses low thermal efficiency in mobile applications by optimizing materials and structures to operate at high temperatures, eliminating water cooling, and recycling waste heat, enhancing efficiency and reducing system weight.
Patent Information
- Application Number
- CN202210493622.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-05-07
AI Technical Summary
Fuel cell power systems in mobile transportation suffer from low thermal efficiency due to heat loss, as thermal energy cannot be effectively converted into kinetic energy, and existing solutions do not adequately address this issue.
A cross-temperature range liquid hydrogen fuel cell power system that operates from room temperature to 240°C, eliminating the water cooling system and incorporating a waste heat recycling system, utilizing nickel-based metals, titanium dioxide-gold/platinum core-shell nanostructure catalysts, and a proton exchange membrane reinforced with alumina or zirconia fibers, along with a liquid hydrogen auxiliary cooling system to manage high temperatures.
Improves thermal efficiency by reducing internal resistance and power loss, allowing for efficient heat recycling and cooling, resulting in increased electrical conversion efficiency and reduced system weight and complexity.
Smart Images

Figure CN114899448B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a cross-temperature liquid hydrogen fuel cell power system. Background Art
[0002] The proton exchange membrane fuel cell (PEMFC) using hydrogen fuel has a good thermal efficiency, about twice that of an internal combustion engine, and the electrical conversion efficiency reaches 50%; of the remaining 50% heat loss, the air cooling system and thermal radiation account for less than 10%, and cannot be recovered and reused, but the remaining 41% of heat loss or 80-90% of the loss is entirely caused by heat loss from liquid cooling (water cooling).
[0003] Since the temperature inside the battery can reach 80°C, in a fixed (ground) power generation system, the problem of heat loss can be solved through combined heat and power. By reprocessing and reusing the water cooling system, the thermal efficiency can be increased by 30% on the basis of the electrical efficiency, so that the overall combined heat and power efficiency can reach an ideal figure of more than 80%. However, as a fuel cell power system used in mobile transportation, thermal energy cannot be converted into effective kinetic energy, and there is a problem of low thermal efficiency, and other innovative means are needed to solve the problem of heat loss. Summary of the invention
[0004] The present invention provides a cross-temperature range liquid hydrogen fuel cell power system, which improves the thermal efficiency of the existing fuel cell power system by performing a high-temperature reaction from room temperature to 240°C, reducing the internal resistance and power loss of the battery, removing the water cooling system including the intercooler and adding a waste heat recycling system.
[0005] In order to achieve the above-mentioned purpose, the present invention provides a cross-temperature range liquid hydrogen fuel cell power system, which includes: a liquid hydrogen tank and a conventional liquid hydrogen gasification and transportation channel, the liquid hydrogen tank is used to store liquid hydrogen, and the conventional liquid hydrogen gasification and transportation channel is connected to the liquid hydrogen tank; a stack, the stack includes a plurality of stacked single cells, the single cell includes a positive bipolar plate, a negative bipolar plate, a gas diffusion layer, a catalyst layer and a proton exchange membrane, the positive bipolar plate has an oxidant channel, the negative bipolar plate has a fuel channel, and the fuel channel is connected to the conventional liquid hydrogen gasification and transportation channel, wherein the materials of the positive bipolar plate and the negative bipolar plate are both nickel-based metals, the oxidant channel and the fuel channel are both arch bridge structures, the gas diffusion layer includes fiber felt and nickel-based metal electroplated on the fiber felt, the catalyst layer is a titanium dioxide-gold / platinum core-shell nanostructure, and the proton exchange membrane is a long fiber reinforced nanoparticle composite membrane; a motor and a rectifier transformer, and the output end of the stack, the rectifier transformer and the motor are connected in sequence.
[0006] Furthermore, both the positive bipolar plate and the negative bipolar plate have a liquid hydrogen auxiliary cooling channel, and the liquid hydrogen auxiliary cooling channel can be connected to the liquid hydrogen tank in an on-off manner.
[0007] Furthermore, the positive bipolar plate includes a positive plate body and a plurality of positive arched plates, the plurality of positive arched plates are arranged on a side of the positive plate body facing the gas diffusion layer, the cavity of each positive arched plate forms an oxidant channel, the positive plate body and the area between two adjacent positive arched plates form a liquid hydrogen auxiliary cooling channel, and the volume ratio of the oxidant channel to the liquid hydrogen auxiliary cooling channel is greater than 4.5; the negative bipolar plate includes a negative plate body and a plurality of negative arched plates, the plurality of negative arched plates are arranged on a side of the negative plate body facing the gas diffusion layer, the cavity of each negative arched plate forms a fuel channel, the negative plate body and the area between two adjacent negative arched plates form a liquid hydrogen auxiliary cooling channel, and the volume ratio of the fuel channel to the liquid hydrogen auxiliary cooling channel is greater than 4.5.
[0008] Furthermore, both the positive bipolar plate and the negative bipolar plate are nickel-based metal arch bridge-type thin sheet structures with surface nitriding, and the thickness of the thin sheet is not higher than 0.3 mm.
[0009] Furthermore, the gas diffusion layer is a nickel-based metal foam structure with surface nitriding, the porosity of the gas diffusion layer is greater than 80%, and the catalyst layer is deposited on the proton exchange membrane by direct spray deposition.
[0010] Further, the titanium dioxide-gold / platinum core-shell nanostructure includes an oxide-free gold nanocore and a single atomic layer of platinum shell deposited on the gold nanocore, and the edges and vertices of the gold nanocore are covered by titanium dioxide.
[0011] Furthermore, the proton exchange membrane is an acetic acid-stabilized nano-lepidocrocite composite membrane reinforced by alumina fiber or zirconia fiber.
[0012] Furthermore, the proton exchange membrane includes a nanoparticle matrix and multiple warp inner cores and multiple weft inner cores arranged in the nanoparticle matrix, the multiple warp inner cores and multiple weft inner cores are orthogonally arranged, the warp inner cores and the weft inner cores are fiber structures, and the warp inner cores and the weft inner cores are formed by single-filament or multi-filament weaving.
[0013] Furthermore, the surfaces of the warp inner core and the weft inner core have a plurality of nanometer-sized protrusions prepared by a deposition method, the protrusions, the warp inner core and the weft inner core are all made of the same material, and the warp inner core and the weft inner core are both provided with pre-fracture notches.
[0014] Furthermore, the cross-temperature zone liquid hydrogen fuel cell power system also includes a volatilization transport channel and a gas collecting tank. The two ends of the volatilization transport channel are respectively connected to the liquid hydrogen tank and the gas collecting tank to collect hydrogen volatilized from the liquid hydrogen tank. The gas collecting tank is connected to the fuel channel of the fuel cell stack.
[0015] Furthermore, the liquid hydrogen tank includes an outer liner, an inner liner and a plurality of support bodies, the inner liner is arranged in the outer liner, the inner liner is filled with liquid hydrogen, the area between the inner liner and the outer liner is a vacuum layer, one end of the support body is connected to the inner wall of the outer liner, and the other end of the support body supports the outer wall of the inner liner; the plurality of support bodies are arranged around the inner liner, the support body is a pseudo-conical shape, aerogel is arranged at one end of the support body facing the inner liner, the aerogel is in contact with the outer wall of the inner liner, and the liquid hydrogen tank also includes a vacuum pump, the vacuum pump is located in the vacuum layer, and the vacuum layer is connected to the inner wall of the outer liner.
[0016] Furthermore, the motor includes a stator structure and a rotor structure, and the rotor structure is rotatably arranged in the stator structure; the stator structure includes a stator amorphous alloy core and a winding wound on the stator amorphous alloy core, and the stator amorphous alloy core is provided with a plurality of liquid hydrogen regeneration cooling channels distributed in the circumferential direction, and the inner wall material of the liquid hydrogen regeneration cooling channel is an aluminum-lithium alloy; the rotor structure includes a silicon steel rotor, a rotor shaft, a magnetic isolation material and a plurality of permanent magnets, the rotor shaft passes through the silicon steel rotor, the magnetic isolation material is arranged around the rotor shaft, and the plurality of permanent magnets are distributed in the silicon steel rotor, each permanent magnet has a liquid hydrogen regeneration cooling channel, and the inner wall material of the liquid hydrogen regeneration cooling channel is an aluminum-lithium alloy.
[0017] Furthermore, the cross-temperature zone liquid hydrogen fuel cell power system also includes a waste heat recycling device, which is connected to the steam outlet of the fuel cell stack to collect and utilize the heat in the steam generated by the fuel cell stack. The waste heat recycling device includes a combined heat and power heating and humidification device and a micro-memory alloy hydraulic engine. Among them, the combined heat and power heating and humidification device performs combined heat and power supply for vehicles in winter to replace air conditioning. The micro-memory alloy hydraulic engine can convert steam into auxiliary kinetic energy, providing free power for all pumps of the entire power system, including hydraulic pumps and pneumatic pumps.
[0018] According to the technical solution of the present invention, a cross-temperature range liquid hydrogen fuel cell power system is provided, and the cross-temperature range liquid hydrogen fuel cell power system includes: a liquid hydrogen tank and a conventional liquid hydrogen gasification and transportation channel, the liquid hydrogen tank is used to store liquid hydrogen, and the conventional liquid hydrogen gasification and transportation channel is connected to the liquid hydrogen tank; a fuel cell stack, the fuel cell stack includes a plurality of stacked single cells, the single cell includes a positive bipolar plate, a negative bipolar plate, a gas diffusion layer, a catalytic layer and a proton exchange membrane, the positive bipolar plate has an oxidant channel, the negative bipolar plate has a fuel channel, and the fuel channel is connected to the conventional liquid hydrogen gasification and transportation channel, wherein the materials of the positive bipolar plate and the negative bipolar plate are both nickel-based metals, the oxidant channel and the fuel channel are both arch bridge structures, the gas diffusion layer includes fiber felt and nickel-based metal electroplated on the fiber felt, the catalytic layer is a core-shell nanostructure, and the proton exchange membrane is an acetic acid-stabilized nano-fibrous iron ore composite membrane reinforced with alumina fiber or zirconium oxide fiber; a motor and a rectifier transformer, and the output end of the fuel cell stack, the rectifier transformer and the motor are connected in sequence. The operating temperature of traditional battery stacks generally does not exceed 80°C, and a water cooling system is required to avoid overheating. In this solution, the materials and structures of each part of the single cell are optimized so that the battery stack can adapt to an operating temperature above 240°C. The water cooling system can be removed in this solution, and the liquid hydrogen refrigeration method can be used to ensure a suitable and high operating temperature, and the high-temperature exhaust gas of the fuel cell is recycled and reused, so that the heat taken away by the cooling system is less, and the heat effectively utilized is increased, thereby improving thermal efficiency. In addition, liquid hydrogen is used as an energy source in this solution, which has a high energy density, and the liquid hydrogen temperature is an ultra-low temperature of 22k, which can be used to efficiently cool the battery stack and the motor in small doses, thereby improving the cooling effect.
[0019] Traditional battery stacks require a large-structure water cooling system to avoid overheating and burning traditional proton exchange membranes. Through this solution, the water cooling system that accounts for about 50% of the battery system volume, including the oxidant intercooler, is eliminated, and the natural temperature rise in the battery is used to improve the power generation efficiency. The simplified on-board ultra-low temperature liquid hydrogen cooling is used as auxiliary and safety temperature control above 240°C, which improves the thermal efficiency of the system and greatly reduces and simplifies the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 A schematic diagram showing the arrangement of a cross-temperature liquid hydrogen fuel cell power system provided by an embodiment of the present invention is shown;
[0022] Figure 2 Shows Figure 1 A cross-sectional view of a single cell in FIG.
[0023] Figure 3 Shows Figure 2 Schematic diagram of the proton exchange membrane in a single cell;
[0024] Figure 4 Shows Figure 3 Schematic diagram of the connection between the longitudinal inner core and the latitudinal inner core in the proton exchange membrane;
[0025] Figure 5 Shows Figure 4 Schematic diagram of the structure of the longitudinal inner core and the latitudinal inner core in the proton exchange membrane;
[0026] Figure 6 Shows Figure 1 A schematic diagram of the stator structure of the motor;
[0027] Figure 7 Shows Figure 1 A schematic diagram of the rotor structure of the motor;
[0028] Figure 8 Shows Figure 1 A cross-sectional view of a liquid hydrogen tank.
[0029] The above drawings include the following reference numerals:
[0030] 10. Liquid hydrogen tank; 11. Outer tank; 12. Inner tank; 13. Support body; 14. Vacuum pump;
[0031] 21. Conventional liquid hydrogen gasification and transportation channel; 22. Liquid hydrogen refrigeration channel; 23. Refrigeration liquid hydrogen gasification and transportation channel; 24. Volatilization transportation channel; 25. Gas collecting tank; 26. Steam and waste gas discharge channel;
[0032] 30. Single cell; 31. Positive bipolar plate; 311. Oxidant channel; 312. Positive plate body; 313. Positive arch plate; 32. Negative bipolar plate; 321. Fuel channel; 322. Negative plate body; 323. Negative arch plate; 33. Gas diffusion layer; 34. Catalytic layer; 35. Proton exchange membrane; 351. Nanoparticle matrix; 352. Longitudinal inner core; 353. Latitudinal inner core; 354. Protrusion; 355. Pre-fracture notch; 36. Liquid hydrogen auxiliary cooling channel;
[0033] 50. Motor; 51. Stator structure; 511. Stator amorphous alloy core; 512. Winding; 52. Rotor structure; 521. Silicon steel rotor; 522. Rotor shaft; 523. Magnetic isolation material; 524. Permanent magnet; 53. Liquid hydrogen regeneration cooling channel;
[0034] 60. Rectifier transformer;
[0035] 70. Waste heat recycling device; 71. Combined heat and power heating and humidification device; 72. Micro memory alloy hydraulic engine. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] like Figures 1 to 8 As shown, an embodiment of the present invention provides a cross-temperature range liquid hydrogen fuel cell power system, which includes: a liquid hydrogen tank 10 and a conventional liquid hydrogen gasification transport channel 21, the liquid hydrogen tank 10 is used to store liquid hydrogen, and the conventional liquid hydrogen gasification transport channel 21 is connected to the liquid hydrogen tank 10; a fuel cell stack, the fuel cell stack includes a plurality of stacked single cells 30, the single cell 30 includes a positive bipolar plate 31, a negative bipolar plate 32, a gas diffusion layer 33, a catalytic layer 34 and a proton exchange membrane 35, the positive bipolar plate 31 has an oxidant channel 311, the negative bipolar plate 32 has a fuel channel 321, and the fuel channel 321 is connected to the conventional liquid hydrogen gasification transport channel 21, wherein the materials of the positive bipolar plate 31 and the negative bipolar plate 32 are both nickel-based metals, the oxidant channel 311 and the fuel channel 321 are both arch bridge structures, and the gas diffusion layer 33 includes a fiber felt and a nickel-based metal electroplated on the fiber felt (specifically nickel-chromium alloy 600, nickel alloy Hastelloy D, pure nickel or 50:50 nickel-chromium alloy), the catalytic layer 34 is a TiO2-Au / Pt core-shell nanostructure, the proton exchange membrane 35 is a long fiber reinforced nanoparticle composite membrane (specifically, an acetic acid-stabilized nano-lepidocrocite composite membrane reinforced with alumina fiber or zirconia fiber), and the proton exchange membrane 35 is a two-dimensional or three-dimensional microstructure; the motor 50 and the rectifier transformer 60, the output end of the fuel cell stack, the rectifier transformer 60 and the motor 50 are connected in sequence.
[0038] The operating temperature of a traditional battery stack generally does not exceed 80°C, and a water cooling system is required to cool it to avoid overheating. In this solution, the materials and structures of each part of the single cell 30 are optimized so that the battery stack can adapt to the non-refrigerated operating temperature above 240°C. In this solution, the water cooling system including the air oxidant intercooler is removed, so that the heat taken away by the cooling system is less, and the heat effectively utilized is increased, thereby improving the thermal efficiency. In addition, liquid hydrogen is used as an energy source in this solution, which has a high energy density and a low temperature of liquid hydrogen, which can cool the battery stack and the motor 50, thereby improving the cooling effect. Specifically, the materials of the positive bipolar plate 31 and the negative bipolar plate 32 are both nickel-based metals, specifically nickel-chromium alloy 600, nickel alloy Hastelloy D, pure nickel or 50:50 nickel-chromium alloy.
[0039] In this embodiment, both the positive bipolar plate 31 and the negative bipolar plate 32 have a liquid hydrogen auxiliary cooling channel 36, which can be connected to the liquid hydrogen tank 10 in an on-off manner. In this way, when the temperature in the single cell 30 is too high and affects normal operation, the low-temperature liquid hydrogen in the liquid hydrogen tank 10 can be directly transported to the inside of the single cell 30 through the liquid hydrogen auxiliary cooling channel 36 to achieve rapid cooling, thereby ensuring reliable operation of the battery stack.
[0040] In the cross-temperature zone heating design, the air oxidant will generate a temperature of about 150°C after being pressurized by a conventional air pressure pump. After the intercooler is eliminated, they will externally heat the low-temperature hydrogen pipeline and bipolar plate before entering the fuel cell to promote rapid temperature rise of the battery. The cross-temperature zone liquid hydrogen fuel cell power system also includes a steam and exhaust gas exhaust channel 26 to exhaust the steam and exhaust gas generated by the stack.
[0041] Some parameters of the cross-temperature liquid hydrogen fuel cell power system are:
[0042] Working temperature: room temperature ~ 400℃ cross-temperature range;
[0043] Starting working temperature: normal temperature;
[0044] High-efficiency working temperature range without refrigeration: 170~240℃;
[0045] Hydrogen working pressure: about 1.4 MPa, mainly realized by high-pressure hydrogen cylinder and pressure-reducing valve;
[0046] Oxygen working pressure: about 1.4 MPa, realized by conventional air pressure pump and eliminating intercooler;
[0047] Average output voltage: 0.8~1.0367V;
[0048] Equivalent voltage: 1.481V;
[0049] System output voltage realization: sine wave inverter or other high-efficiency boost converter;
[0050] Battery stack power: 10 (small passenger car) - 10000kw (all-electric ship);
[0051] Electrical conversion efficiency: greater than 70%;
[0052] Stack power density: greater than 2.09kw / kg;
[0053] Fuel used: liquid hydrogen;
[0054] Proton exchange membrane: 2D microstructure of γ-FeOOH nanoparticles stabilized by acetic acid reinforced by alumina fibers or zirconia fibers;
[0055] Bipolar plate: nickel-based metal arch bridge type ultra-thin plate, plate thickness 0.1-0.3mm; specifically nickel-chromium alloy 600, nickel alloy Hastelloy D, pure nickel or 50:50 nickel-chromium alloy;
[0056] Gas diffusion layer: nickel-based metal foam; specifically nickel-chromium alloy 600, nickel alloy Hastelloy D, pure nickel or 50:50 nickel-chromium alloy;
[0057] Catalyst: TiO2-Au / Pt core-shell nanostructure (titanium oxide-gold / platinum), the optimal Pt particles are 1 to 1.5 nm or atomic arrangement;
[0058] End plate and shell: S-glass continuous fiber reinforced S-glass matrix multifunctional composite plate;
[0059] Motor: Liquid hydrogen regenerative cooling semi-superconducting motor;
[0060] Liquid hydrogen tank: stainless steel A286.
[0061] The operating temperature of traditional PEMFC (proton exchange membrane fuel cell) generally does not exceed 80℃. There are also high-temperature PEMFCs designed to increase efficiency, which can reach 180-200℃, but their overheated startup temperature is not suitable for cars or vehicles because they cannot be started in a short time. The cross-temperature design refers to a new type of PEMFC that can use normal temperature for quick startup and can complete 160-240℃ high-temperature and efficient climbing in a very short time after startup.
[0062] 41% of the heat in PEMFC is taken away by the water cooling system. The reason why the water cooling system is needed is that the operating temperature of the traditional proton exchange membrane perfluorosulfonic acid membrane can only be around 80°C. After completely eliminating the water cooling equipment, not only can the efficiency be greatly increased, but also the weight can be greatly reduced and simplified (the water cooling system usually accounts for about 50% of the volume of the fuel cell system).
[0063] The temperature of the gasified liquid hydrogen input into the fuel cell has risen to around -40°C. Even so, it can still have a decisive natural cooling effect on the fuel cell.
[0064] After this solution cancels the water cooling / liquid cooling system, we will allow the battery to continue to heat up from room temperature after startup, convert the heat energy taken away by liquid cooling (water cooling) into heating energy and efficiency energy, and finally maintain the operating temperature below 240°C through small doses of high-efficiency liquid hydrogen cooling. If there is a need to continue to increase the efficiency, after upgrading the heat resistance temperature of the rubber system seal, the non-cooling temperature can be increased to more than 300°C and ultimately shall not be higher than the hydrogen environment ferroferric oxide reduction temperature of lepidocrocite in the new oxide proton exchange membrane of 400°C.
[0065] Therefore, a reduced version of the liquid hydrogen channel will be retained on the bipolar plate. This is a backup channel to prevent the system from overheating. When the system is overheated, it can be temporarily cooled down quickly. When the backup channel is opened, the liquid hydrogen will take a shortcut and pass through the liquid hydrogen backup channel at a low temperature below -250°C, then enter the gasification channel and then enter the fuel channel. This design greatly increases the input amount and volume energy density of the fuel and oxidant.
[0066] The converted heat energy can generate an additional electrical conversion efficiency of more than 20%.
[0067] The advantage of the cross-temperature zone design is that it can be started at any time without affecting the normal operation of the vehicle. When the starting temperature is at ambient temperature, the electrical conversion efficiency is less than 50%. However, as the electrochemical reaction releases heat energy and the external heat conduction and internal heating of the pressurized high-temperature oxidizer of the intercooler produce temperature rise, the efficiency will continue to rise and the temperature can reach 170°C in a very short time.
[0068] When PEMFC is running at full power, its internal humidity often reaches 100%, so the membrane electrode is often flooded, affecting normal operation. When this solution is running at more than 100℃, the water generated by electrochemistry begins to convert into steam. At this time, flooding will no longer occur, and the battery efficiency will increase due to steam, humidity and temperature.
[0069] In this embodiment, the cross-temperature zone liquid hydrogen fuel cell power system further includes a liquid hydrogen refrigeration channel 22, a refrigerated liquid hydrogen gasification delivery channel 23, and the liquid hydrogen tank 10, the liquid hydrogen refrigeration channel 22, the liquid hydrogen auxiliary cooling channel 36, the refrigerated liquid hydrogen gasification delivery channel 23, the conventional liquid hydrogen gasification delivery channel 21 and the fuel channel 321 are sequentially connected. In this way, when the liquid hydrogen entering the liquid hydrogen auxiliary cooling channel 36 exceeds the set high temperature, the single cell 30 can be quickly cooled first, and then enter the conventional liquid hydrogen gasification delivery channel 21 for gasification, and then enter the fuel channel 321 to participate in the reaction.
[0070] Traditional bipolar plates need to provide large-volume water-cooling channels, so the volume ratio of their gas channels (hydrogen and air) / water-cooling channels (the location of the liquid hydrogen cooling channel in this design) is 1:1, and traditional bipolar plates are wavy or square.
[0071] The gas channel / cooling channel volume ratio of our innovatively designed arch bridge bipolar plate is 9:1. The bipolar plate is arch bridge shaped. This design is based on the following two points:
[0072] The cooling capacity of liquid hydrogen (ultra-low temperature) is dozens of times that of water, so 1 / 10 of the volume is sufficient for the emergency backup cooling system (only triggered at 98% of the designed peak temperature). The arch bridge design greatly increases the volume and input capacity of the hydrogen and air oxidant channels, with an enhancement of up to 80%. This capacity will directly increase the electrical conversion efficiency by 5-7%.
[0073] Materials and anti-oxidation corrosion ability: The bipolar plate uses a nickel-based metal sheet structure to replace the graphite structure, achieving the triple design requirements of high-strength anti-oxidation, ultra-high conductivity and low cost. The bipolar plate serves as the overall support structure of the battery, as well as the outer wall for the flow of hydrogen and oxygen and the discharge channel for water and excess gas. It must retain sufficient specific strength for high heat, high humidity, oxidation and hydrogen environments. Due to the extremely harsh oxidation environment inside the PEM, any stainless steel and aluminum-lithium alloy will produce very serious oxygen corrosion (more and more oxides are produced on the surface, which greatly reduces the conductivity and eventually leads to the end of the battery life). Although graphite does not produce this corrosion, its conductivity is extremely low; the two best ultra-high oxidation resistance in metals are nickel, chromium and titanium, and at present, the first two metal materials are one of the best options for dealing with ultra-high oxidation reactions inside the PEM and maintaining high conductivity. Among them, the conductivity of nickel is far better than that of chromium, especially the elongation at break of chromium is 0, which is a highly brittle metal and therefore cannot complete the structural work alone.
[0074] The bipolar plate also serves as a current collection terminal and must have excellent conductivity. The use of graphite as a bipolar plate material for traditional fuel cells is not a good choice because the conductivity of graphite is far inferior to that of conductive metals, and its stress tolerance is very poor and it is very easy to break. The resistivity of graphite is: 910μΩ·cm, the resistivity of nickel is: 7.98μΩ·cm, and the resistance of nickel-based metal is 105μΩ·cm. Since conductivity is the reciprocal of resistivity, the conductivity of nickel is 114 times that of graphite, and nickel-based metal is 8.66 times that of graphite.
[0075] After surface nitriding treatment of nickel-based metal, the PEM corrosion current density of nickel-based metal is 0.018μA cm 2 , which is 14-16 μA cm of graphite plate 2 0.12%.
[0076] This solution also includes airflow input and output channels that cooperate with the liquid hydrogen cooling unit. The shapes of the airflow input and output channels are: the y-direction is the original arch bridge type, and the x-direction can choose a variable-section straight-through type, a multi-channel serpentine type, or a 3D mesh flow field based on comprehensive performance and processing cost.
[0077] Since nickel is relatively expensive (more than three times that of chromium), it should be used as a lightweight hollow structure to reduce costs when used as an automotive component. The arch bridge type ultra-thin hollow structure is prepared by pressure welding + gluing of metal sheets / strips at a lower cost. The weight of the bipolar plate of the present invention is no more than 71% of the weight of the battery stack, which is lower than 80% of the aluminum alloy bipolar plate and 90% of the graphite bipolar plate. The nickel-based ultra-thin sheet prepared by the roller pressing method can further reduce the weight of the bipolar plate to less than 55% when the stress condition process of 0.15 to 0.25 mm is completed;
[0078] Specifically, Figure 2 As shown, the positive bipolar plate 31 includes a positive plate body 312 and a plurality of positive arched plates 313, wherein the plurality of positive arched plates 313 are arranged on one side of the positive plate body 312 facing the gas diffusion layer 33, and the cavity of each positive arched plate 313 forms an oxidant channel 311, and the area between the positive plate body 312 and two adjacent positive arched plates 313 forms a liquid hydrogen auxiliary cooling channel 36, and the volume ratio of the oxidant channel 311 to the liquid hydrogen auxiliary cooling channel 36 is greater than 4.5, for example, 9. Correspondingly, the negative bipolar plate 32 includes a negative plate body 322 and a plurality of negative arch plates 323, wherein the plurality of negative arch plates 323 are arranged on one side of the negative plate body 322 facing the gas diffusion layer 33, wherein the cavity of each negative arch plate 323 forms a fuel channel 321, and the negative plate body 322 and the area between two adjacent negative arch plates 323 form a liquid hydrogen auxiliary cooling channel 36, and the volume ratio of the fuel channel 321 to the liquid hydrogen auxiliary cooling channel 36 is greater than 4.5, for example, 9.
[0079] Through the above arrangement, the cross-sectional area of the oxidant channel 311 and the fuel channel 321 is increased, thereby increasing the volume of the oxidant channel 311 and the fuel channel 321, and the use of the arched plate can improve the structural strength of the single cell 30. In this solution, since the liquid hydrogen cooling effect is high, the volume of the liquid hydrogen auxiliary cooling channel 36 can be set to be relatively small, reducing the occupied space and improving the ability to transport air, hydrogen and air cooling.
[0080] Furthermore, the positive bipolar plate 31 and the negative bipolar plate 32 are both surface-nitrided nickel-based metal arch bridge-type thin sheet structures, and the thickness of the thin sheet is not more than 0.3 mm. The above structure can reduce the weight of the single cell 30 while ensuring the structural strength and improve the energy density.
[0081] In this embodiment, the gas diffusion layer 33 is a nickel-based metal foam structure with surface nitriding, the porosity of the gas diffusion layer 33 is greater than 80%, and the catalyst layer 34 is deposited on the proton exchange membrane 35 by direct spray deposition. This is conducive to the uniform distribution of hydrogen and oxygen and improves the reaction effect.
[0082] The material of the catalyst layer 34 is TiO2-Au / Pt.
[0083] Traditional PEMFC uses carbon paper or woven carbon cloth as the gas diffusion layer. Both of them do not have hydrogen embrittlement reaction. Their maximum operating temperature is far more than 170℃, and they can work in high humidity and high corrosion environment. However, the disadvantages of carbon paper or woven carbon cloth are also obvious, that is, their conductivity is much worse than metal, which will affect the battery's electrical conversion efficiency. We innovatively use nickel-based metal foam made by metal deposition method to replace carbon paper and carbon cloth.
[0084] The gas diffusion layer must have sufficient porosity to ensure that the gas can pass smoothly and have space to absorb water (or steam) and complete the conductive task. The maximum porosity of metal foam made by metal deposition method is as high as 99%. The specific processing technology is: using electrodeposition technology, electroplating nickel alloy powder on the fiber and completing sintering; the steps are: substrate pretreatment; conductive treatment (chemical plating or coating with conductive glue); electroplating; reduction sintering; surface nitriding.
[0085] Catalysts are the main reaction level for fuel cells to generate current due to electrochemistry. At present, Pt platinum systems still dominate PEMFC catalysts. Other non-platinum materials do not have comparable catalytic performance and comprehensive performance. We can know the performance of catalysts through two indicators: the oxygen reduction ORR performance and specific activity of the catalyst; and the ability of the battery to save platinum per kw.
[0086] Traditional catalysts waste a lot of platinum because only the Pt atoms in the surface layer can react with the gas. In theory, the Pt in the middle part of the material is wasted. The core-shell structure is currently the most advanced PEMFC catalyst structure because it can maximize the surface area utilization of platinum atoms and even achieve a single-layer Pt atomic arrangement if the process permits.
[0087] The edges and vertices of the core in the TiO2-Au / Pt core-shell nanostructure are covered with refractory metal oxide TiO2, and a single atomic layer of Pt shell is deposited on the oxide-free Au gold nanocore; the oxide on the edges and vertices can induce the Pt shell to produce high catalyst stability and activity. The catalytic layer 34 adopts a joint process with the membrane electrode: the catalyst is deposited on the membrane using a direct spray deposition method and hot pressed.
[0088] In this scheme, since most of the platinum is replaced by titanium oxide and gold, the TiO2-Au / Pt core-shell nanostructure can reduce the platinum density power of 0.5gPt / kw to below 0.2g / kw, and theoretically can reach 0.05g / kw; based on the average use of a 10kw fuel cell per passenger car, the global annual passenger car production is about 70 million. Even if all vehicles are replaced with PEMFC power in the future, with a platinum usage rate of 0.2g / kw, the total usage is still 27% less than the global annual platinum production (190 tons). Therefore, the platinum density power below 0.2g / kw has the significance of sustainable development, while above 0.5g / kw is not sustainable.
[0089] The Pt monolayer shell deposited on the Au sites has about 13 times higher ORR performance and 5 times higher specific activity than the commercial Pt / C catalyst. Durability testing showed no activity loss after 10,000 potential cycles from 0.6 to 1.0 V. The superior activity and durability of the TiO2-Au / Pt core-shell nanostructured catalyst originate from the protective titanium oxide located at the most soluble edge and vertex sites and the active and stable Pt shell supported by Au.
[0090] In this embodiment, the proton exchange membrane 35 includes a nanoparticle matrix 351 and a plurality of warp inner cores 352 and a plurality of weft inner cores 353 arranged in the nanoparticle matrix 351, the plurality of warp inner cores 352 and the plurality of weft inner cores 353 are orthogonally arranged, the warp inner cores 352 and the weft inner cores 353 are fiber structures, and the warp inner cores 352 and the weft inner cores 353 are formed by single-filament or multi-filament weaving.
[0091] Optionally, the volume ratio of the sum of the volumes of the multiple warp inner cores 352 and the multiple weft inner cores 353 to the volume of the nanoparticle matrix 351 is 2:8; the volume ratio of the multiple warp inner cores 352 and the multiple weft inner cores 353 is 1:1, and the stress ratio of the multiple warp inner cores 352 and the multiple weft inner cores 353 is 1:1.
[0092] Specifically, the proton exchange membrane 35 is an acetic acid-stabilized γ-FeOOH nanoparticle material reinforced by alumina fiber or zirconia fiber, or a SPEEK / PBI composite material, or a SPEEK / BPO4 organic-inorganic composite material.
[0093] In this embodiment, the surfaces of the warp inner core 352 and the weft inner core 353 have a plurality of nano-sized protrusions 354 prepared by a deposition method (such as 3D printing), the protrusions 354, the warp inner core 352 and the weft inner core 353 are all made of the same material, and the warp inner core 352 and the weft inner core 353 are both provided with pre-fracture notches 355.
[0094] The PEMFC membrane is a layer of solid electrolyte, whose function is to transfer hydrogen ions with high conductivity and to prevent gas from passing through as much as possible, hence the name "proton exchange membrane". Therefore, the standards for measuring the membrane are mainly hydrogen ion conductivity, air permeability and survivability (thermal environment, water environment and tensile stress, etc.).
[0095] Traditional PEMFC uses perfluorosulfonic acid membrane, the hydrogen ion conductivity of which reaches 0.1S / cm-1, the air permeability is very low, and the working tensile strength can reach 20-30mpa.
[0096] The acetic acid-stabilized γ-FeOOH nanoparticles we prepared have much higher hydrogen ion conductivity than perfluorosulfonic acid membranes, but due to the high brittleness / low toughness and low stress strength of ceramics, it is difficult to make them into membranes. Therefore, we specially designed alumina fiber or zirconia fiber reinforced acetic acid-stabilized γ-FeOOH nano two-dimensional or three-dimensional microstructures to enhance the comprehensive capacity of the membrane.
[0097] The matrix material is acetic acid-stabilized gamma-FeOOH nanoparticles; the process is a deposition method, a fiber coating method-magnetron sputtering method or a hot isostatic pressing method.
[0098] Alumina fiber or zirconia fiber has strong tensile strength and toughness (zirconia), excellent insulation ability (does not allow electrons to pass through); as well as high-temperature oxidation resistance, steam and chemical corrosion resistance. Its thermal expansion coefficient of 8-12μm is very close to that of γ-FeOOH nanoparticles stabilized by acetic acid. Zirconia fiber has higher selection advantages than alumina, especially in thermal expansion coefficient and toughness, but the price is much higher.
[0099] The nanoparticle two-dimensional microstructure consists of a longitudinal stress inner core, a latitudinal stress inner core, and a γ-FeOOH nanoparticle matrix; the inner core material and process are: alumina or zirconia fiber, two-dimensional weaving molding + laser printing or other deposition methods to prepare nano-protrusions of the same material.
[0100] The volume ratio of the inner core to the matrix is 2:8; the two-dimensional warp / weft volume ratio and stress ratio of the inner core part is 1:1; the strength of the two-dimensional microstructure of γ-FeOOH nanoparticles reinforced with alumina fibers and stabilized by acetic acid exceeds 223 MPa, which is 9 times that of traditional PEM.
[0101] The pull-out force generated after the inner core breaks and the huge friction between the broken inner core and the matrix enhance the fracture work and fracture toughness of the material; we design many nano-sized protrusions on the surface of the inner core to generate more friction with the matrix during the process of the inner core breaking and pulling out. In order to allow more and more reasonably sized broken inner cores to participate in the pull-out friction, we design a pre-fracture notch in the inner core to ensure that the fracture behavior occurs at the notch, making the fracture behavior more controllable.
[0102] During processing, the matrix is densified by hot isostatic pressing or vacuum hot pressing sintering. Reference data: The matrix is sintered at 500℃ or above for more than 160min;
[0103] In this scheme, the hydrogen ion conductivity of the new membrane: the proton conductivity of the acetic acid-stabilized γ-FeOOH nanoparticles can be higher than 0.5S·cm-1, and the proton conductivity of the designed composite material at 170°C and 40-100% RH = 0.4-0.5S·cm-1; therefore, it is 4-5 times that of the traditional perfluorosulfonic acid membrane.
[0104] In this solution, the thickness and gas permeability of the new membrane are:
[0105] Thickness: 10~20μm.
[0106] Gas / liquid permeability: designed to be less than 0.5%; inversely proportional to the material density function, since the two-dimensional microstructure of acetic acid-stabilized γ-FeOOH nanoparticles reinforced by alumina or zirconia fibers is a densified solid structure, its gas permeability resistance is greater than or equal to that of traditional membranes.
[0107] Steam corrosion resistance of the new membrane: it can work for a long time in a 100% steam oxidation environment;
[0108] High temperature resistance of the new membrane: Acetic acid-stabilized γ-FeOOH nanoparticles reinforced with alumina fibers or zirconia fibers as ceramics can complete long-term high-temperature oxidation tasks below 400°C.
[0109] The flexural strength, compressive strength and hydrogen embrittlement resistance of composite materials all meet the design requirements.
[0110] The life design in this scheme is explained below.
[0111] At present, the actual average life of vehicle-mounted (or airborne / ship-mounted) PEM fuel cells is only about 3000 to 5000 hours. The main life parameters are composed of the anti-aging parameters of the electrode (catalyst), PEM membrane, bipolar plate, gas diffusion layer and sealing system; among them, the proportion of catalyst aging is the largest, about 25.5%, and the aging of the PEM membrane accounts for more than 17.5%.
[0112] Aging parameters of the Pt catalyst: Pt separation 64%; Pt coarsening 30%; Pt dissolution 6%.
[0113] The main cause of Pt aging: carbon corrosion. Due to the large amount of carbon impurities in the gas hydrogen preparation process, it is the first parameter leading to Pt aging, especially the direct use of hydrocarbons such as natural gas and methane. Although they are reformed inside the battery, the carbon corrosion index will still increase exponentially; water shock and erosion. The PEM environment is full of water. Water shock mainly washes away Pt particles and gathers them on large particles, thereby causing coarsening and re-separation.
[0114] Anti-aging design of Pt: a. Liquid hydrogen with a purity of almost 100% is used to replace gaseous hydrogen, so there is almost no C and CO inside the fuel cell. The purification process of hydrogen liquefaction can completely avoid this problem and greatly improve the life of Pt; b. The CT-PEMFC design is adopted to increase the operating temperature to above the steam temperature of water. Once the water becomes steam, water shock and flooding will no longer exist. This design can also greatly improve the life of Pt; c. We expect to increase the life of Pt in vehicle-mounted (or airborne / ship-mounted) PEM fuel cells to 8000-15000h.
[0115] The main causes of PEM membrane aging are: mechanical loss and thermal loss, and the two reinforce each other; the tensile strength, fracture toughness and high-temperature oxidation ability of traditional perfluorosulfonic acid membranes are very low, which is the main reason why the perfluorosulfonic acid membranes become thinner and even break.
[0116] The acetic acid-stabilized γ-FeOOH nano-two-dimensional microstructure reinforced with alumina fiber or zirconia fiber has a yield strength higher than 223 MPa and high toughness, and its theoretical mechanical life is more than 9 times that of traditional membranes.
[0117] The acetic acid-stabilized γ-FeOOH nano-two-dimensional microstructure reinforced with alumina fiber or zirconia fiber has high temperature resistance below 400°C and maintains extremely strong thermal fatigue life in high-temperature fuel cells, and the thermal fatigue stress is far from the fatigue temperature (above 800°C) of the oxide fiber that provides structural mechanical properties; we expect to increase the working life of the new γ-FeOOH nano-two-dimensional microstructure membrane reinforced with alumina fiber or zirconia fiber to more than 15,000 hours.
[0118] Anti-aging design of bipolar plates and gas diffusion layers: The aging of bipolar plates and gas diffusion layers still focuses on mechanical loss and oxidation problems.
[0119] For graphite / carbon felt materials with low conductivity, high corrosion resistance, low stress and low toughness: Due to the extremely low tensile strength and toughness of graphite and carbon felt, mechanical loss accounts for an important proportion of the life loss of traditional bipolar plates and gas diffusion layers. Graphite is prone to fracture, cracks, decomposition, etc., which can directly lead to the reduction of the life of the fuel cell; in addition, the oxidation problem of graphite and carbon (further reduction of conductivity) cannot be ignored;
[0120] For metal materials with high conductivity, high stress and high toughness: oxides will deposit on the surface of bipolar plates and gas diffusion layers and the amount of deposits will increase. The conductivity of bipolar plates and gas diffusion layers will be gradually weakened. Therefore, the life of metal bipolar plates and gas diffusion layers does not refer to mass loss (oxidation loss or oxide increase will also account for a part) but refers to the end of battery life due to the loss of conductivity caused by oxide deposition.
[0121] Anti-oxidation design of metal bipolar plates and gas diffusion layers:
[0122] Among metals, probably only nickel and chromium can cope with the ultra-high oxidation reaction inside PEM and maintain high electrical conductivity. Among them, the electrical conductivity of nickel is far better than that of chromium. In particular, the elongation at break of chromium is 0, which is a highly brittle metal and therefore cannot complete structural work alone. We use nickel-based metals as bipolar plates, which have high conductivity, high-temperature resistance to oxidation and corrosion, and tensile strength and toughness that are more than ten times that of graphite. We use nickel metal foam as the gas diffusion layer, which has the quadruple properties of high conductivity, high-temperature resistance to oxidation and corrosion, tensile strength and toughness. We expect to increase the life of the bipolar plates and gas diffusion layers of vehicle-mounted (or airborne / ship-mounted) PEM fuel cells to more than 15,000 hours.
[0123] Furthermore, the cross-temperature zone liquid hydrogen fuel cell power system also includes a volatilization transport channel 24 and a gas collecting tank 25. The two ends of the volatilization transport channel 24 are respectively connected to the liquid hydrogen tank 10 and the gas collecting tank 25 to collect hydrogen volatilized from the liquid hydrogen tank 10. The gas collecting tank 25 is connected to the fuel channel 321 of the fuel cell stack.
[0124] Through the above design, we make the volatile hydrogen go through an independent volatile transport channel, and instead of discharging it, we pressurize it and input it into the gas collecting tank. After accumulating a sufficient dose in the gas collecting tank, it is directly input into the single battery and generates electricity. Most of this electricity is used for the circulation of the liquid hydrogen tank micro-automatic refrigeration system. This design is automated, similar to the metabolic system of a smart car, which will not be affected by shutting down the car.
[0125] Designed maximum volatility = 0.2% / day = 28 g / day;
[0126] The designed pressure of the gas collecting tank is = 10-20 standard atmospheres = about 1-2mp;
[0127] Output power generation rhythm = automatic power generation once every 4 hours on average.
[0128] The volatilization cycle design has the following effects:
[0129] a. Allow liquid hydrogen vehicles to be parked in underground garages and enclosed spaces without emitting volatile gases (if hydrogen leaks, the sensor will notify the car to sound the horn for a long time, the system and the owner will also receive a warning, and the car will be moved out of the enclosed area), while currently low-temperature fuel vehicles (LNG, liquid hydrogen, etc.) cannot enter underground parking lots;
[0130] b. The volatile electricity is used for the vacuum pump of the automatic control system of the liquid hydrogen tank to complete the self-circulation;
[0131] c. The remaining volatile electricity will be mainly used to charge the battery (not plugged in);
[0132] d. In case of excess volatile electricity (battery energy exceeds 80%), the car will automatically start to adjust the temperature in the car, with a design temperature of 20-25 degrees Celsius, so that the owner can get a comfortable temperature environment when entering the car. This design makes the car an organism with metabolism; this function has options, and the owner can choose temperature priority control, that is, all or most of the volatile electricity is used to maintain the temperature in the car.
[0133] like Figure 8 As shown, the liquid hydrogen tank 10 includes an outer liner 11, an inner liner 12 and a plurality of supports 13. The inner liner 12 is arranged in the outer liner 11. The inner liner 12 is filled with liquid hydrogen. The area between the inner liner 12 and the outer liner 11 is a vacuum layer. One end of the support body 13 is connected to the inner wall of the outer liner 11, and the other end of the support body 13 supports the outer wall of the inner liner 12. The plurality of supports 13 are arranged around the inner liner 12. The support body 13 is a pseudo-conical shape. An aerogel is arranged at one end of the support body 13 facing the inner liner 12. The aerogel is in contact with the outer wall of the inner liner 12. The liquid hydrogen tank 10 also includes a vacuum pump 14. The vacuum pump 14 is located in the vacuum layer, and the vacuum layer is connected to the inner wall of the outer liner 11.
[0134] In this embodiment, the liquid hydrogen tank 10 adopts a double-layer design of an outer liner 11 and an inner liner 12 with a vacuum layer formed in the middle. Since the insulation coefficient of the vacuum layer is 0.006w / m·k, the insulation capacity is 2-20 times that of other insulation materials. The vacuum layer is used to insulate the liquid hydrogen to avoid the phenomenon of excessive heating and volatilization of the liquid hydrogen, while reducing the weight of the liquid hydrogen tank 10.
[0135] In this embodiment, the direct contact point between the support body 13 and the inner liner 12 is the highest heat transfer point, and heat is easily transferred to the inner liner 12, causing the liquid hydrogen to volatilize. Aerogel is arranged at the contact position between the support body 13 and the inner liner 12 to have an insulating effect on the connection position between the support body 13 and the inner liner 12, thereby preventing the liquid hydrogen in the inner liner 12 from volatilizing due to heat. The support body 13 is designed to be a pseudo-conical shape, which, on the basis of ensuring the stress at the contact position between the support body 13 and the inner liner 12, realizes the miniaturization of the contact area, further ensuring the insulation effect. Furthermore, this embodiment realizes the triggered vacuum control of the vacuum layer through the vacuum pump 14, thereby ensuring the reliability of the insulation of the vacuum layer.
[0136] In the process of using gaseous hydrogen and other non-hydrogen fuels, the battery will suffer from carbon poisoning, which is caused by the combined reaction of the carbon element in the impure hydrogen content of the fuel and the catalyst. Severe C poisoning will make the battery efficiency low and reduce the battery life. Although it can be prevented by upgrading the catalyst, that is, adding other more expensive elements in the platinum family, it will obviously increase manufacturing costs and can only delay but not completely eliminate C poisoning.
[0137] Since liquid hydrogen has ultra-high purity (much higher than commercial gaseous hydrogen), the use of liquid hydrogen can completely eliminate C poisoning and greatly extend the life of the battery. If the life of a transportation fuel cell is 4,000 hours, then the use of liquid hydrogen without C poisoning PEMFC can double it.
[0138] Due to the need for direct contact with hydrogen, hydrogen fuel cell materials must face the problem of hydrogen embrittlement, which can cause a significant stress drop and create danger. Many people do not know and regard hydrogen embrittlement as an ordinary corrosion problem. However, the response to hydrogen embrittlement is completely different from ordinary corrosion protection.
[0139] In this design, all materials that come into contact with hydrogen have the ability to prevent hydrogen embrittlement.
[0140] Inner diameter: xm;
[0141] Liner length: ym;
[0142] Outer diameter: x+0.07m;
[0143] Outer liner length: y+0.07m (excluding valve);
[0144] Middle layer: vacuum, 20-30mm;
[0145] Middle layer insulation coefficient: 0.006w / m·k;
[0146] Vacuum degree control of the middle layer: 0.005pa, use a micro vacuum pump to control the vacuum degree of the middle layer for a long time;
[0147] Inner and outer liner support: 8 thermal insulation support structures (point contact type);
[0148] Support material and insulation coefficient: Aerogel is used in the inner liner contact area, with an insulation coefficient of 0.012w / m·k; the main support material is a carbon-based composite material;
[0149] Liquid hydrogen storage tank inner and outer liner material: stainless steel A-286 (density 7.8g / cm 3 , tensile strength 1400mp), the main principle of material selection is to prevent hydrogen embrittlement;
[0150] Hydrogen weight ratio (ratio of liquid hydrogen to total tank weight): greater than 0.2;
[0151] Designed volatility = 0.2% / day = 28 g / day;
[0152] Temperature inside the tank: less than 20.35K;
[0153] Internal pressure: 5 atmospheres;
[0154] External pressure: 1 atmosphere;
[0155] Stress and strain: Maximum stress and maximum strain failure criteria, the maximum allowable strain is 0.006m / m.
[0156] Like all cryogenic fuels, the vaporization of liquid hydrogen is difficult to avoid. We deal with it in the following ways:
[0157] 1) The liquid hydrogen tank is double-layered, with the middle layer being a vacuum design. The vacuum is used to insulate the liquid hydrogen to prevent it from overheating and volatilizing and to reduce the weight of the liquid hydrogen tank; (the insulation coefficient of the vacuum is 0.006w / m·k, and the insulation capacity is 2-20 times that of other insulation materials);
[0158] 2) A micro vacuum pump (without contacting the inner tank) is used in the middle layer of the liquid hydrogen tank to perform air pressure-triggered vacuum control on the middle layer, and the trigger vacuum degree is designed to be 0.005pa;
[0159] 3) The insulation support structure is a high-conductivity point because it is in direct contact with the inner liner. Since the support stress of the inner and outer liner is not high, the contact surface material and contact surface area can be controlled. The contact surface material is aerogel, and the insulation coefficient is 0.012w / m·k, which is the top insulation material second only to vacuum insulation. The contact surface type is pseudo-conical, which minimizes the contact surface while ensuring the stress.
[0160] like Figure 6 and Figure 7As shown, the motor 50 includes a stator structure 51 and a rotor structure 52, and the rotor structure 52 is rotatably arranged in the stator structure 51; the stator structure 51 includes a stator amorphous alloy core 511 and a winding 512 wound on the stator amorphous alloy core 511, and the stator amorphous alloy core 511 is circumferentially provided with a plurality of liquid hydrogen regeneration cooling channels 53, and the inner wall material of the liquid hydrogen regeneration cooling channel 53 is an aluminum-lithium alloy; the rotor structure 52 includes a silicon steel rotor 521, a rotor shaft 522, a magnetic isolation material 523 and a plurality of permanent magnets 524, the rotor shaft 522 passes through the silicon steel rotor 521, the magnetic isolation material 523 is arranged around the rotor shaft 522, and the plurality of permanent magnets 524 are distributed in the silicon steel rotor 521, and each permanent magnet 524 has a liquid hydrogen regeneration cooling channel 53, and the inner wall material of the liquid hydrogen regeneration cooling channel 53 is an aluminum-lithium alloy.
[0161] Optionally, the material of the winding 512 is copper wire or superconducting composite wire, the material of the permanent magnet 524 is neodymium iron boron or superconducting material, and the magnetic isolation material 523 is polyimide added with silicon dioxide.
[0162] By distributing a plurality of liquid hydrogen regeneration cooling channels 53 in the circumferential direction of the stator amorphous alloy core 511, the cooling effect on the stator structure 51 can be improved, thereby improving the magnetic force of the structure. Moreover, the inner wall material of the liquid hydrogen regeneration cooling channel 53 is aluminum-lithium alloy, which avoids the hydrogen embrittlement problem of other materials. At the same time, the thermal conductivity of aluminum-lithium alloy is 5 times that of stainless steel, another anti-hydrogen embrittlement material. This ability can quickly take away the heat inside the motor pole. The material of the winding 512 can be copper wire or superconducting composite wire. Among them, using ultra-fine wire AC superconducting composite wire instead of copper wire, adding a liquid hydrogen refrigeration environment consistent with the rotor structure, can achieve full superconductivity.
[0163] Furthermore, through the above arrangement, liquid hydrogen can flow into the liquid hydrogen regeneration cooling channel 53 of the permanent magnet 524, thereby cooling the rotor structure 52. The material of the permanent magnet 524 can be neodymium iron boron or a superconducting material. When a superconducting material is used and a low temperature environment is achieved through liquid hydrogen, the energy density can be greatly improved.
[0164] Power of the above motor 50: 80kw (passenger car) - 28.926MW;
[0165] Voltage: 400-3000V;
[0166] Motor type: regeneratively cooled permanent magnet synchronous motor;
[0167] Energy-to-weight ratio: 7kw / kg;
[0168] Stator core: Co72Fe3P16B6AI3 (Co amorphous alloy);
[0169] Stator winding: copper wire;
[0170] Insulation material: polyimide with added silicon dioxide; temperature resistance level 280℃;
[0171] Rotor: Hiperco (high-strength iron-cobalt alloy);
[0172] Rotor permanent magnet: Sm2Co17 cobalt rare earth permanent magnet;
[0173] Liquid hydrogen channel: aluminum-lithium alloy.
[0174] Innovation of liquid hydrogen regenerative cooling motor: There are two ways to reduce weight. One is to increase the magnetic force of the magnetic structure of the motor of the same weight to achieve the purpose of weight reduction. The other is to directly reduce weight by reducing the material density. In addition to the shell material, the motor needs to use the first weight reduction method.
[0175] Temperature control has an absolute advantage in increasing magnetic efficiency. There are currently two ways of cooling magnetic poles on the market. One is air cooling, which is to increase the air volume of the motor fan, but the efficiency is not good. Placing the motor in the direction of the engine fan can only increase the magnetic efficiency by a small amount, but because the motor is large in size, it will directly affect the engine's air duct output; the second is to use a liquid nitrogen environment to design high-temperature superconducting materials, but the temperature of liquid nitrogen is about 77K, and the magnetic force of the high-temperature superconducting material cannot be brought into play to the optimal level.
[0176] Since this power system uses liquid hydrogen as fuel, we have designed a very practical liquid hydrogen regeneration cooling function. Liquid hydrogen is introduced into the motor before entering the fuel cell for gasification, forming a regeneration cycle, which greatly reduces the magnetic pole temperature of the stator and rotor and improves the magnetic energy. This design directly increases the energy-to-weight ratio of the motor to 7kw / kg; the channel is made of an aluminum-lithium alloy body, avoiding the hydrogen embrittlement problem of other materials. At the same time, the thermal conductivity of the aluminum-lithium alloy is 3 times that of stainless steel, another anti-hydrogen embrittlement material. This ability can quickly take away the heat inside the motor's magnetic poles.
[0177] The material of the stator structure is Co72Fe3P16B6AI3 (Co amorphous alloy), and the main parameters are as follows:
[0178] Density greater than 9.5g / cm 3 ;
[0179] Yield strength 4580mpa;
[0180] Thermal expansion coefficient 5.99×10^-6;
[0181] Relative magnetic permeability is greater than 10^6;
[0182] Coercivity 10^(-2.7) / A / cm (significantly reduces electrical loss);
[0183] Designed to increase the liquid hydrogen regeneration cooling channel, lower the temperature of the iron core and copper core, reduce losses and increase efficiency;
[0184] The material selection criteria are to minimize the coercive force and enhance the magnetic permeability to increase efficiency and reduce losses. Co amorphous alloy is one of the most ideal choices.
[0185] High-purity copper wire is used for the stator winding; a liquid hydrogen regenerative cooling channel is added, and the channel material is an aluminum-lithium alloy. Liquid hydrogen cooling replaces ventilation cooling to obtain maximum magnetic force and minimum copper loss; combined with the rotor permanent magnet cooling function, a 7kw / kg energy-to-weight ratio is achieved, reducing the motor weight to 4132kg.
[0186] The rotor material is Hiperco (high-strength iron-cobalt alloy), and the main parameters are as follows:
[0187] Magnetic induction: 1.9-2.35T;
[0188] Tensile strength and yield strength: 1340mpa / 1280mpa;
[0189] Density: 8.2g / cm 3 ;
[0190] Coercivity: not higher than 32HC;
[0191] Speed: System output speed 2600-3673R / min, using variable speed gearbox;
[0192] The first element is to select a soft magnet with super tensile yield strength to increase the speed and power and minimize coercivity and losses.
[0193] The material of the rotor permanent magnet is Sm2Co17 cobalt rare earth permanent magnet, and the main parameters are as follows:
[0194] Magnetic direction: Yes, the powder has magnetic direction before pressing but is affected by pressing;
[0195] Magnetic energy (BHmax): 240KJ / m 3 ;
[0196] Density: 8.2g / cm 3 ;
[0197] Tensile strength: 3430mpa;
[0198] Thermal expansion coefficient: 131-511 μm / m·k;
[0199] Designed to add liquid hydrogen regenerative cooling channels to maximize the magnetic energy of the permanent magnets (higher than 240KJ / m 3), and at the same time, ultra-low temperature is used to control the Co rare earth so that it does not expand violently and cause breaking stress to the channel and rotor (the linear expansion coefficient of Co rare earth is more than 10 times that of metal);
[0200] The selection criteria are the maximum magnetic energy for the same volume and the ability to withstand ultra-high rotation speeds;
[0201] Regenerative cooling channel material: aluminum-lithium alloy.
[0202] In this embodiment, the cross-temperature zone liquid hydrogen fuel cell power system also includes a waste heat recycling device 70, which is connected to the steam outlet of the battery stack to collect and utilize the heat in the steam generated by the battery stack. Specifically, the waste heat recycling device 70 includes a cogeneration heating and humidification device 71 and a micro-memory alloy hydraulic engine 72. When the battery stack in this scheme is working normally, the temperature of the steam generated in the single cell 30 can reach above 160°C, and the thermal recycling of this part can further improve the efficiency of the system. The steam generated by the battery stack can be collected by the waste heat recycling device 70 and exchanged with the components that need to be heated, thereby realizing heat recycling. Specific examples are as follows:
[0203] 1. Best application: combined heat and power in winter (through combined heat and power heating and humidification device 71):
[0204] PEM's combined heat and power can easily increase thermal efficiency to 80%. However, as an on-board application, this goal can only be achieved in winter. That is to say, unlike electric vehicles that need to use a lot of electricity to drive the air conditioner in the car in winter, cars using this solution can use hot air completely free of charge throughout the winter through a heat recycling distributor (that is, a waste heat recycling device), and have a free air humidification function.
[0205] 2. Other thermal energy reuse:
[0206] Through the micro memory alloy hydraulic engine 72, it can replace or partially replace the electrical energy required by the vehicle brakes. It can drive the pump body in the vehicle free of charge, including the air compression pump (reducing 5-10% of the system efficiency loss) and the hydraulic pump, or directly generate auxiliary power.
[0207] 3. Comprehensive efficiency enhancement:
[0208] Through the above scheme, we can increase the overall thermal efficiency by more than 10% regardless of winter or summer, exceeding the ideal target of 80%.
[0209] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cross-temperature liquid hydrogen fuel cell power system, characterized in that: The cross-temperature liquid hydrogen fuel cell power system comprises: A liquid hydrogen tank (10) and a conventional liquid hydrogen gasification transport channel (21), wherein the liquid hydrogen tank (10) is used to store liquid hydrogen, and the conventional liquid hydrogen gasification transport channel (21) is in communication with the liquid hydrogen tank (10); A fuel cell stack, the fuel cell stack comprising a plurality of stacked single cells (30), the single cells (30) comprising a positive bipolar plate (31), a negative bipolar plate (32), a gas diffusion layer (33), a catalyst layer (34) and a proton exchange membrane (35), the positive bipolar plate (31) having an oxidant channel (311), the negative bipolar plate (32) having a fuel channel (321), the fuel channel (321) being connected to the conventional liquid hydrogen gasification transport channel (21), wherein the materials of the positive bipolar plate (31) and the negative bipolar plate (32) are both nickel-based metals, the oxidant channel (311) and the fuel channel (321) are both arch bridge structures, the gas diffusion layer (33) comprises a fiber felt and a nickel-based metal electroplated on the fiber felt, the catalyst layer (34) is a titanium dioxide-gold / platinum core-shell nanostructure, and the proton exchange membrane (35) is a long fiber reinforced nanoparticle composite membrane; A motor (50) and a rectifier transformer (60), wherein the output end of the battery stack, the rectifier transformer (60) and the motor (50) are connected in sequence.
2. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The positive bipolar plate (31) and the negative bipolar plate (32) both have a liquid hydrogen auxiliary cooling channel (36), and the liquid hydrogen auxiliary cooling channel (36) can be connected to the liquid hydrogen tank (10) in an on-off manner.
3. The cross-temperature liquid hydrogen fuel cell power system according to claim 2, characterized in that: The positive bipolar plate (31) comprises a positive plate body (312) and a plurality of positive arched plates (313), wherein the plurality of positive arched plates (313) are arranged on a side of the positive plate body (312) facing the gas diffusion layer (33), the cavity of each positive arched plate (313) forms an oxidant channel (311), the area between the positive plate body (312) and two adjacent positive arched plates (313) forms a liquid hydrogen auxiliary cooling channel (36), and the volume ratio of the oxidant channel (311) to the liquid hydrogen auxiliary cooling channel (36) is greater than 4.5; The negative bipolar plate (32) comprises a negative plate body (322) and a plurality of negative arched plates (323), wherein the plurality of negative arched plates (323) are arranged on a side of the negative plate body (322) facing the gas diffusion layer (33), the cavity of each negative arched plate (323) forms a fuel channel (321), the negative plate body (322) and the area between two adjacent negative arched plates (323) form a liquid hydrogen auxiliary cooling channel (36), and the volume ratio of the fuel channel (321) to the liquid hydrogen auxiliary cooling channel (36) is greater than 4.
5.
4. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The positive bipolar plate (31) and the negative bipolar plate (32) are both surface-nitrided nickel-based metal arch bridge-type thin sheet structures, and the thickness of the thin sheet is not greater than 0.3 mm.
5. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The gas diffusion layer (33) is a nickel-based metal foam structure with surface nitriding, the porosity of the gas diffusion layer (33) is greater than 80%, and the catalyst layer (34) is deposited on the proton exchange membrane (35) by direct spray deposition.
6. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The titanium dioxide-gold / platinum core-shell nanostructure comprises an oxide-free gold nanocore and a single atomic layer platinum shell deposited on the gold nanocore, and the edges and vertices of the gold nanocore are covered by titanium dioxide.
7. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The proton exchange membrane (35) is an acetic acid-stabilized nano-lepidocrocite composite membrane reinforced by aluminum oxide fibers or zirconium oxide fibers.
8. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The proton exchange membrane (35) comprises a nanoparticle matrix (351) and a plurality of warp inner cores (352) and a plurality of weft inner cores (353) arranged in the nanoparticle matrix (351); the plurality of warp inner cores (352) and the plurality of weft inner cores (353) are arranged orthogonally; the warp inner cores (352) and the weft inner cores (353) are fiber structures; the warp inner cores (352) and the weft inner cores (353) are formed by single-filament or multi-filament weaving.
9. The cross-temperature liquid hydrogen fuel cell power system according to claim 8, characterized in that: The surfaces of the warp inner core (352) and the weft inner core (353) are provided with a plurality of nano-sized protrusions (354) prepared by a deposition method; the protrusions (354), the warp inner core (352) and the weft inner core (353) are all made of the same material; and the warp inner core (352) and the weft inner core (353) are both provided with pre-fracture notches (355).
10. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The cross-temperature liquid hydrogen fuel cell power system further comprises a volatilization transport channel (24) and a gas collecting tank (25), wherein two ends of the volatilization transport channel (24) are respectively connected to the liquid hydrogen tank (10) and the gas collecting tank (25) to collect hydrogen volatilized from the liquid hydrogen tank (10), and the gas collecting tank (25) is connected to a fuel channel (321) of the fuel cell stack.
11. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The liquid hydrogen tank (10) comprises an outer liner (11), an inner liner (12) and a plurality of support bodies (13); the inner liner (12) is arranged in the outer liner (11); the inner liner (12) is filled with liquid hydrogen; the area between the inner liner (12) and the outer liner (11) is a vacuum layer; one end of the support body (13) is connected to the inner wall of the outer liner (11); the other end of the support body (13) supports the outer wall of the inner liner (12); a plurality of support bodies (13) are arranged around the inner liner (12); the support body (13) is a pseudo-conical shape; an aerogel is arranged at one end of the support body (13) facing the inner liner (12); the aerogel is in contact with the outer wall of the inner liner (12); the liquid hydrogen tank (10) further comprises a vacuum pump (14); the vacuum pump (14) is located in the vacuum layer; the vacuum layer is connected to the inner wall of the outer liner (11).
12. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The motor (50) comprises a stator structure (51) and a rotor structure (52), wherein the rotor structure (52) is rotatably arranged in the stator structure (51); the stator structure (51) comprises a stator amorphous alloy core (511) and a winding (512) wound on the stator amorphous alloy core (511), wherein the stator amorphous alloy core (511) is provided with a plurality of liquid hydrogen regeneration cooling channels (53) distributed in a circumferential direction, and the inner wall material of the liquid hydrogen regeneration cooling channel (53) is an aluminum-lithium alloy; the rotor structure (52 ) comprises a silicon steel rotor (521), a rotor shaft (522), a magnetic isolation material (523) and a plurality of permanent magnets (524), wherein the rotor shaft (522) passes through the silicon steel rotor (521), the magnetic isolation material (523) is arranged around the rotor shaft (522), the plurality of permanent magnets (524) are distributed in the silicon steel rotor (521), each of the permanent magnets (524) has a liquid hydrogen regeneration cooling channel (53), and the inner wall material of the liquid hydrogen regeneration cooling channel (53) is an aluminum-lithium alloy.
13. The cross-temperature liquid hydrogen fuel cell power system according to claim 1, characterized in that: The cross-temperature liquid hydrogen fuel cell power system also includes a waste heat recycling device (70), which is connected to the steam outlet of the fuel cell stack to collect and utilize the heat in the steam generated by the fuel cell stack. The waste heat recycling device (70) includes a combined heat and power heating and humidification device (71) and a micro memory alloy hydraulic engine (72).